2008
DOI: 10.1016/j.brainres.2008.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking α-tocopherol transfer protein gene have severe α-tocopherol deficiency in multiple regions of the central nervous system

Abstract: Ataxia with vitamin E deficiency is caused by mutations in α-tocopherol transfer protein (α-TTP) gene and it can be experimentally generated in mice by α-TTP gene inactivation (α-TTP-KO). This study compared α-tocopherol (α-T) concentrations of five brain regions and of four peripheral organs from 5 months old, male and female, wild-type (WT) and α-TTP-KO mice. All brain regions of female WT mice contained significantly higher α-T than those from WT males. α-T concentration in the cerebellum was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…[39]). It is also interesting to note that significant gender-specific differences in tissue a-tocopherol levels have been reported [52][53][54]. We suggest that potential interaction effects between vitamin E supplementation and other experimental variables require further investigation in light of these reported findings.…”
Section: Impact Of Vitamin E Supplementation On Rodent Lifespanmentioning
confidence: 86%
“…[39]). It is also interesting to note that significant gender-specific differences in tissue a-tocopherol levels have been reported [52][53][54]. We suggest that potential interaction effects between vitamin E supplementation and other experimental variables require further investigation in light of these reported findings.…”
Section: Impact Of Vitamin E Supplementation On Rodent Lifespanmentioning
confidence: 86%
“…Interestingly, following just one week of development, the adult pattern was already established for ascorbate and α-tocopherol in the P14 brain with few exceptions. Overall, these results can be explained by the developmental stage of a brain region, such as the varying neuronal and glial densities and the stage of myelination at a given postnatal age [15, 16, 19]. However, this is unlikely to be the sole explanation, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…The litter size was culled to eight on P3. Only males were studied, in order to avoid the confounding effects of sex on the antioxidants [16, 25]. Animals in Aim 1 were killed after overnight fasting (n=6 at P14 and P60, and n=14 at P7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After atocopherol enters the brain, aTTP may have an important role in supplying a-tocopherol to neurons and glial cells. We and others showed that a-tocopherol in the brain was almost depleted in aTTP -/-mice and was markedly decreased even in aTTP -/-mice fed an a-tocopherol-rich diet resulting in increased serum a-tocopherol (Yokota et al, 2001;Gohil et al, 2008). aTTP is expressed in astrocytes (Hosomi et al, 1998), and cholesterol, as a major lipid, is transferred to neurons and glial cells from astrocytes by HDL-like particles synthesized in astrocytes (Pfrieger, 2003;Vance et al, 2005;Herz and Chen, 2006).…”
Section: Introductionmentioning
confidence: 99%